General kleski, Ludwik Mieroslawski, 1814-1878. - Zychowski, Marian (Warszawa, Iskry, 1965)
Biography of the 19th century Polish general.
Keywords: Mieroslawski, Ludwik, -- 1814-1878.; Poland. -- Armia -- Biography; Generals -- Poland -- Biography